PENINGKATAN HASIL BELAJAR MELALUI MODEL PROBLEM BASED LEARNING KELAS V SDN KARANGANYAR GUNUNG 02 - Retno Wahyuning Wardhany; Mudzanatun; Nur Riskiyati (Jurnal Bionatural, 2024)
This research aims to determine the improvement of students' learning outcomes in Pancasila and Civic Education using the Problem Based Learning approach with the assistance of Happy Note media. Conducted in class V of SDN Karanganyar Gunung 02 with 28 student participants, the study lasted for two cycles, each comprising two sessions. The dependent variable was students' learning achievement, while the independent variable was the implementation of PBL aided by Happy Note media. Data collection methods included interviews, observations, tests, and documentation, with data analysis employing both quantitative and qualitative approaches. Results indicate that after implementing the PBL model with Happy Note media in Cycle I, students' learning achievement reached a score of 68 with a mastery level of 60%. Improvement in learning outcomes and critical thinking abilities in Cycle II showed an increase in scores to 79, with a student mastery rate of 79%. Thus, the application of PBL with the assistance of Happy Note media can enhance students' learning outcomes in PPKN subject in class V of SDN Karanganyar Gunung 02 Semarang.